PHENOMENOGRAPHICAL COLLOQUIES OF THE HALLYU WAVE AMONG SELECTED STUDENTS OF TAYTAY SENIOR HIGH SCHOOL, PHILIPPINES - Blas, Fe Atanacio; Erestain, Charelome O. (PEOPLE: International Journal of Social Sciences, 2020)
The invasion of the South Korean culture in the Philippines has spanned in almost three decades where the former started exporting their drama series that caught a wide public attention in Philippine TV on 1990’s. The evolution since then was foreseen inevitable that in fact, from 1.0 (K-drama), 2.0 (K-pop), 3.0 (K-culture), it continues to evolve into 4.0 (K-technology and online games) and the developing and ongoing 5.0 (a possible pan-pacific cross over). In this study, the Hallyu wave was carefully delineated by the researchers thru extensive literature reviews and further affirmed by the colloquies of the selected senior High School participants using the Phenomenographical approach. A Focus-Group Discussion was conducted that anchored with the theories of Soft Power (Nye, 1990), Desire Fulfillment (Heathwood, 2014), Cultural Hybridization (Ryoo, 2009), and Cultural Intermediaries (Maguire and Matthews, 2012). From the results of the colloquies, the researchers were able to bracket and expound qualitatively the following analysis and synthesis of results based from the responses of the participants: struggle, ingenuity of ways, influences, inexplicable satisfaction, fandom bonding, the irony of situation, inspired by idol and dream away. These results paralleled the theories used to support the study and as such, proved the continuing wave and fever of the Hallyu culture in the Philippine archipelago. In future studies, the researchers recommend that a western counterpart in the area of adaptation and appreciation could be explored, both quantitatively and qualitatively.